Diastereoselective synthesis of [1]rotaxanes via an active metal template strategy. Issue 7 (8th January 2021) - Pairault, Noël; Bessaguet, Adrien; Barat, Romain; Frédéric, Lucas; Pieters, Grégory; Crassous, Jeanne; Opalinski, Isabelle; Papot, Sébastien
Abstract : The first diastereoselective synthesis of mechanically planar chiral [1]rotaxanes has been achieved using the active template Cu-mediated alkyne–azide cycloaddition reaction. Abstract : Despite the impressive number of interlocked molecules described in the literature over the past 30 years, only a few stereoselective syntheses of mechanically chiral rotaxanes have been reported so far. In this study, we present the first diastereoselective synthesis of mechanically planar chiral [1]rotaxanes, that has been achieved using the active template Cu-mediated alkyne–azide cycloaddition reaction. This synthetic method has been applied to the preparation of a [1]rotaxane bearing a labile stopper that can then be substituted without disruption of the mechanical bond. This approach paves the way for the synthesis of a wide variety of mechanically planar chiral [1]rotaxanes, hence allowing the study of the properties and potential applications of this class of interlocked molecular architectures.